A thin section micromorphology photomicrographs dataset of the infilling of the Sennacherib Assyrian canal system (Kurdistan Region of Iraq) - Stefano Costanzo; Luca Forti; Daniele Morandi Bonacossi; Andrea Zerboni (Data in Brief, 2023)
Here we present a compendium of 212 photographs of archaeological soils and sediments thin sections (micrographs) from the backfill of the Sennacherib Assyrian canal system of Northern Mesopotamia. The micrographs were produced using an optical petrographic microscope (Olympus BX41) mounting a digital camera (Olympus E420) for image acquisition. The dataset is composed of two folders containing (1) every micrograph in full resolution JPEG, and (2) a PDF file with scale bars and brief captions for each one. The dataset represents a photographic comparison collection for individuals working on similar geoarchaeological contexts and can be used for the composition of figures in novel publications, as well as being the first example of published large compendium for shared use in the field of archaeology.